2008
DOI: 10.1002/hbm.20658
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity during visual versus kinesthetic imagery: An fMRI study

Abstract: Although there is ample evidence that motor imagery activates similar cerebral regions to those solicited during actual movements, it is still unknown whether visual (VI) and kinesthetic imagery (KI) recruit comparable or distinct neural networks. The present study was thus designed to identify, through functional magnetic resonance imaging at 3.0 Tesla in 13 skilled imagers, the cerebral structures implicated in VI and KI. Participants were scanned in a perceptual control condition and while physically execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
392
3
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(459 citation statements)
references
References 90 publications
25
392
3
13
Order By: Relevance
“…As a result, the correlation between the BCI classifier and the KI score was lower for the GOI task than for the SI task. A possible explanation might be that very 'good' imagers already had good kinaesthetic imagination and the presence of an object diverted them from kinaesthetic to a visual imagery, which activated different areas of the cortex [Neuper et al 2005, Guillot et al 2009]. This hypothesis was supported by the results of the analysis of the ERS/ERD maps of participants with the worst and best KI during SI and GOI.…”
Section: Disucssion and Conclusionmentioning
confidence: 81%
“…As a result, the correlation between the BCI classifier and the KI score was lower for the GOI task than for the SI task. A possible explanation might be that very 'good' imagers already had good kinaesthetic imagination and the presence of an object diverted them from kinaesthetic to a visual imagery, which activated different areas of the cortex [Neuper et al 2005, Guillot et al 2009]. This hypothesis was supported by the results of the analysis of the ERS/ERD maps of participants with the worst and best KI during SI and GOI.…”
Section: Disucssion and Conclusionmentioning
confidence: 81%
“…Patients were instructed to give their best to execute the movement. However, they were discouraged to try so hard that movement of other body parts would occur; (4 and 5) For motor imagery with the right/left hand (Imagery(R)/Imagery(L), respectively) participants were instructed to engage in kinesthetic motor imagery (Guillot et al, 2009; 2006) of the same wrist movement as in Execution; (6) For movement observation (Observation) participants were instructed to attend to a video clip showing a hand (Fig. 2) which moved in the same way as required by the Execution condition; (7 and 8) There were two passive movement conditions.…”
Section: Task and Proceduresmentioning
confidence: 99%
“…Improved methods to measure brain activity, including functional magnetic resonance imagining (fMRI) and transcranial magnetic stimulation (TMS), have shown that motor imagery and observation of actions, can, when used effectively, activate the neural motor system in a way that overlaps significantly with that activated during actual movement [3][4][5][6][7]. When physical movement is impossible, or perhaps very difficult, in the early stages following a brain injury, observation of relevant movements and task-specific motor imagery offer potential avenues to activate the neural motor system without physical movement needing to occur and is, therefore, not reliant on there being some level of residual function [1].…”
Section: Introductionmentioning
confidence: 99%